HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG KANKER SERVIKS DENGAN MINAT PENGGUNAAN VAKSIN HPV - Dessy Hidayati Fajrin (ITKM WIDYA CIPTA HUSADA, 2019)
Cervical cancer is the most gynecologic carcinoma of the 5 types of cancer that occurs in women. Obtained an increased risk of cervical cancer occurs in women under 25 years even those who are still in high school (teenage girls). Primary prevention can be done by avoiding the causative factors and vaccinating HPV. Research on adolescent girls' problems about cervical cancer with this teen's interest in using the HPV vaccine in class XI students at SMAN 2 Sampang. The research method uses cross sectional analytics, the population in this study is the teenage girls of class XI at SMAN 2 Sampang with a sample of 20 teenage girls with simple random sampling. The research instrument used a questionnaire as primary data. The statistical test used was the Spearman Rating with α = 0.05 and obtained ρcalculation = 0.761> ρtable = 0.45 with significance ρ = 0.01 <α. The results showed 65% of young women had enough knowledge about cervical cancer and 70% of young women were not interested in using the HPV vaccine.